2016
DOI: 10.1371/journal.pone.0157344
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Genetic Susceptibility: A Systematic Review and Meta-Analyses of Recent Evidence

Abstract: IntroductionCervical cancer (CC) has one of the highest mortality rates among women worldwide. Several efforts have been made to identify the genetic susceptibility factors underlying CC development. However, only a few polymorphisms have shown consistency among studies.Materials and MethodsWe conducted a systematic review of all recent case-control studies focused on the evaluation of single nucleotide polymorphisms (SNPs) and CC risk, stringently following the “PRISMA” statement recommendations. The MEDLINE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Genome-wide association studies identified cervical cancer susceptibility variants across different populations [23]. Therefore, the input of these and other polymorphic variants, may reflect the interindividuality of response in women with cervical cancer.…”
Section: Lactobacilli Enhance Reactive Oxygen Species and The Role Ofmentioning
confidence: 99%
“…Genome-wide association studies identified cervical cancer susceptibility variants across different populations [23]. Therefore, the input of these and other polymorphic variants, may reflect the interindividuality of response in women with cervical cancer.…”
Section: Lactobacilli Enhance Reactive Oxygen Species and The Role Ofmentioning
confidence: 99%
“…p21 is the major downstream effector of p53, which can act as a mediator between p53, DNA damage and repair and cell‐cycle inhibition . Due to the complex function of p21, p21 exhibits both tumor suppressor and oncogenic attributes . Several studies have been reported the effects of P21 polymorphisms on the function of its protein and may contribute to cancer susceptibility .…”
Section: Discussionmentioning
confidence: 99%
“…To date, over 30 genes have been studied for their role in cervical cancer risk and these include, Bid, BRIP1, Caspase 8, CCR2, CTLA4, CYP1A1, EXO1, FASLG, FASR, HOTAIR, IFN gamma, PARP1, XRCC1, MDM2, IL10, IL12, HLA B/C, MTHFR, Tap2, TNF-a, TLR9, p16, PIK3CA, p21, and p53 Martínez-Nava et al, 2016;Mehta et al, 2015;Mei et al, 2014;Dos Santos et al, 2016;Sousa et al, 2011;Tsakogiannis et al, 2017;and Wang et al, 2017). Of these, genes only nine have been researched in African populations, highlighting a big gap in cervical cancer molecular epidemiology studies in a continent where 90% of the cervical cancer-related deaths are predicted (MboubaBouassa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While these other factors increase the risk of developing cervical cancer, high-risk HPV (hr-HPV) subtypes have been identified as the only definitive etiological factor for cervical intraepithelial neoplasia (CIN) and cervical cancer (Martínez-Nava et al, 2016). HPV deoxyribonucleic acid (DNA) encodes three oncoproteins E5, E6, and E7 that deregulate the function of major histocompatibility complex I, p53, and retinoblastoma (Di Maio and Petti, 2013;Tomaic, 2016).…”
Section: Etiology Of Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation